Click here to load reader

Skeptical Math

  • View
    202

  • Download
    1

Embed Size (px)

Text of Skeptical Math

  • 1. X^6X^7= X^9/X^3= X^-2= x^6 x^4 = X^6X^7= X^9/X^3= X^-2=

2. X^6X^7= X^9/X^3= X^-2= x^6 x^4 = X^6X^7= X^9/X^3= X^-2= 3. X^6X^7= X^9/X^3= X^-2= x^6 x^4 = X^6X^7= X^9/X^3= X^-2= 4. X^6X^7= X^9/X^3= X^-2= x^6 x^4 = X^6X^7= X^9/X^3= X^-2= 5. X^6X^7= X^9/X^3= X^-2= x^6 x^4 = X^6X^7= X^9/X^3= X^-2= 6. X^6X^7= X^9/X^3= X^-2= x^6 x^4 = X^6X^7= X^9/X^3= X^-2= 7. X^6X^7= X^9/X^3= X^-2= x^6 x^4 = X^6X^7= X^9/X^3= X^-2= 8. X^6X^7= X^9/X^3= X^-2= x^6 x^4 = X^6X^7= X^9/X^3= X^-2= 9. X^6X^7= X^9/X^3= X^-2= x^6 x^4 = X^6X^7= X^9/X^3= X^-2= 10. X^6X^7= X^9/X^3= X^-2= x^6 x^4 = X^6X^7= X^9/X^3= X^-2= 11. X^6X^7= X^9/X^3= X^-2= x^6 x^4 = X^6X^7= X^9/X^3= X^-2= 12. X^6X^7= X^9/X^3= X^-2= x^6 x^4 = X^6X^7= X^9/X^3= X^-2= 13. X^6X^7= X^9/X^3= X^-2= x^6 x^4 = X^6X^7= X^9/X^3= X^-2= 14. X^6X^7= X^9/X^3= X^-2= x^6 x^4 = X^6X^7= X^9/X^3= X^-2= 15. X^6X^7= X^9/X^3= X^-2= x^6 x^4 = X^6X^7= X^9/X^3= X^-2= 16. X^6X^7= X^9/X^3= X^-2= x^6 x^4 = X^6X^7= X^9/X^3= X^-2= 17. X^6X^7= X^9/X^3= X^-2= x^6 x^4 = X^6X^7= X^9/X^3= X^-2= 18. X^6X^7= X^9/X^3= X^-2= x^6 x^4 = X^6X^7= X^9/X^3= X^-2= 19. X^6X^7= X^9/X^3= X^-2= x^6 x^4 = X^6X^7= X^9/X^3= X^-2= 20. X^6X^7= X^9/X^3= X^-2= x^6 x^4 = X^6X^7= X^9/X^3= X^-2= 21. X^6X^7= X^9/X^3= X^-2= 22. X^6X^7= X^9/X^3= X^-2= 23. X^6X^7= X^9/X^3= X^-2= 24. X^6X^7= X^9/X^3= X^-2= 25. X^6X^7= X^9/X^3= X^-2= 26. X^6X^7= X^9/X^3= X^-2= 27. X^6X^7= X^9/X^3= X^-2= 28. X^6X^7= X^9/X^3= X^-2= 29. X^6X^7= X^9/X^3= X^-2= 30. X^6X^7= X^9/X^3= X^-2= 31. X^6X^7= X^9/X^3= X^-2= 32. X^6X^7= X^9/X^3= X^-2= 33. X^6X^7= X^9/X^3= X^-2= 34. X^6X^7= X^9/X^3= X^-2= 35. X^6X^7= X^9/X^3= X^-2= 36. X^6X^7= X^9/X^3= X^-2= 37. X^6X^7= X^9/X^3= X^-2= 38. X^6X^7= X^9/X^3= X^-2= 39. X^6X^7= X^9/X^3= X^-2= 40. X^6X^7= X^9/X^3= X^-2= 41. X^6X^7= X^9/X^3= X^-2= 42. X^6X^7= X^9/X^3= X^-2= 43. X^6X^7=X X^9/X^3= X^-2= 44. X^6X^7=X^6+ X^9/X^3= X^-2= 45. X^6X^7=X^6+7=X X^9/X^3= X^-2= 46. X^6X^7=X^6+7=X^13 X^9/X^3= X^-2= 47. X^6X^7=X^6+7=X^13 X^9/X^3= X^-2= 48. X^6X^7=X^6+7=X^13 X^9/X^3= X^-2= 49. X^6X^7=X^6+7=X^13 X^9/X^3=X X^-2= 50. X^6X^7=X^6+7=X^13 X^9/X^3=X^9 X^-2= 51. X^6X^7=X^6+7=X^13 X^9/X^3=X^9-3 X^-2= 52. X^6X^7=X^6+7=X^13 X^9/X^3=X^9-3= X^-2= 53. X^6X^7=X^6+7=X^13 X^9/X^3=X^9-3=X X^-2= 54. X^6X^7=X^6+7=X^13 X^9/X^3=X^9-3=X^6 X^-2= 55. X^6X^7=X^6+7=X^13 X^9/X^3=X^9-3=X^6 X^-2= 56. X^6X^7=X^6+7=X^13 X^9/X^3=X^9-3=X^6 X^-2= 57. X^6X^7=X^6+7=X^13 X^9/X^3=X^9-3=X^6 X^-2= 1 58. X^6X^7=X^6+7=X^13 X^9/X^3=X^9-3=X^6 X^-2= 1 X 59. X^6X^7=X^6+7=X^13 X^9/X^3=X^9-3=X^6 X^-2= 1 X^2 Sk 60. X^6X^7=X^6+7=X^13 X^9/X^3=X^9-3=X^6 X^-2= 1 X^2 Skep 61. X^6X^7=X^6+7=X^13 X^9/X^3=X^9-3=X^6 X^-2= 1 X^2 SkepTIC 62. X^6X^7=X^6+7=X^13 X^9/X^3=X^9-3=X^6 X^-2= 1 X^2 SkepTICal 63. SkepTICal X^6X^7=X^6+7=X^13 X^9/X^3=X^9-3=X^6 X^-2= 1 X^2 64. SkepTICal X^6X^7=X^6+7=X^13 X^9/X^3=X^9-3=X^6 X^-2= 1 X^2 P 65. SkepTICal X^6X^7=X^6+7=X^13 X^9/X^3=X^9-3=X^6 X^-2= 1 X^2 Pe 66. SkepTICal X^6X^7=X^6+7=X^13 X^9/X^3=X^9-3=X^6 X^-2= 1 X^2 Peng 67. SkepTICal X^6X^7=X^6+7=X^13 X^9/X^3=X^9-3=X^6 X^-2= 1 X^2 Pengui 68. SkepTICal X^6X^7=X^6+7=X^13 X^9/X^3=X^9-3=X^6 X^-2= 1 X^2 Penguin 69. SkepTICal X^6X^7=X^6+7=X^13 X^9/X^3=X^9-3=X^6 X^-2= 1 X^2 Penguin 70. SkepTICal X^6X^7=X^6+7=X^13 X^9/X^3=X^9-3=X^6 X^-2= 1 X^2 Penguin 71. Penguin SkepTICal X^6X^7=X^6+7=X^13 X^9/X^3=X^9-3=X^6 X^-2= 1 X^2 72. Penguin SkepTICal X^6X^7=X^6+7=X^13 X^9/X^3=X^9-3=X^6 X^-2= 1 X^2 73. Penguin SkepTICal X^6X^7=X^6+7=X^13 X^9/X^3=X^9-3=X^6 X^-2= 1 X^2 74. Penguin SkepTICal X^6X^7=X^6+7=X^13 X^9/X^3=X^9-3=X^6 X^-2= 1 X^2 75. Penguin SkepTICal X^6X^7=X^6+7=X^13 X^9/X^3=X^9-3=X^6 X^-2= 1 X^2 Meh.

Search related